Nucleotide alterations in the HLA-C class I gene can cause aberrant splicing and marked changes in RNA levels in a polymorphic context-dependent manner - Mizutani, Akiko; Suzuki, Shingo; Shigenari, Atsuko; Sato, Tadayuki; Tanaka, Masafumi; Kulski, Jerzy K.; Shiina, Takashi (Frontiers in Immunology, 2024)
Polymorphisms of HLA genes, which play a crucial role in presenting peptides with diverse sequences in their peptide-binding pockets, are also thought to affect HLA gene expression, as many studies have reported associations between HLA gene polymorphisms and their expression levels. In this study, we devised an ectopic expression assay for the HLA class I genes in the context of the entire gene, and used the assay to show that the HLA-C*03:03:01 and C*04:01:01 polymorphic differences observed in association studies indeed cause different levels of RNA expression. Subsequently, we investigated the C*03:23N null allele, which was previously noted for its reduced expression, attributed to an alternate exon 3 3' splice site generated by G/A polymorphism at position 781 within the exon 3. We conducted a thorough analysis of the splicing patterns of C*03:23N, and revealed multiple aberrant splicing, including the exon 3 alternative splicing, which overshadowed its canonical counterpart. After confirming a significant reduction in RNA levels caused by the G781A alteration in our ectopic assay, we probed the function of the G-rich sequence preceding the canonical exon 3 3' splice site. Substituting the G-rich sequence with a typical pyrimidine-rich 3' splice site sequence on C*03:23N resulted in a marked elevation in RNA levels, likely due to the enhanced preference for the canonical exon 3 3' splice site over the alternate site. However, the same substitution led to a reduction in RNA levels for C*03:03:01. These findings suggested the dual roles of the G-rich sequence in RNA expression, and furthermore, underscore the importance of studying polymorphism effects within the framework of the entire gene, extending beyond conventional minigene reporter assays.